Cardiac Lymphoma Diagnosed by Multi-Modality Imaging: A Case Report - Yang, Dayan; Wu, Tangna; Gao, Lini; Liu, Lili; Liu, Fujin; Jing, Xiangxiang (Frontiers in Cardiovascular Medicine, 2022)
A 79-year-old female patient who presented with a cardiac mass detected by conventional echocardiography was ultimately diagnosed with a malignant tumor by myocardial contrast echocardiography. A positron emission tomography/computed tomography examination showed tumors in the right atrium consistent with the findings of the contrast-enhanced ultrasound. Finally, the patient was confirmed by pathology to have cardiac lymphoma. Because no lesions were found elsewhere in the body, primary cardiac lymphoma was diagnosed by combining multi-modal imaging examination and pathological examination. Although conventional echocardiography may identify a cardiac mass, it is difficult to identify whether they are malignant or not. Myocardial contrast echocardiography helps to identify the location, shape, and size of the mass, its relationship with the surrounding tissue, and evaluate its blood supply. Thus, this imaging modality is of great value for identifying the likely etiology of a cardiac mass. Multi-modal imaging is complementary to echocardiography for determining the location of cardiac masses, invasion of surround structures, extra cardiac spread, and determination of whether a mass is likely benign or malignant. Multi-modality imaging provides an important basis for clinical treatment and decision-making.